Early administration of inhaled nitric oxide to children with acute respiratory distress syndrome and its effects on oxygenation and ventilator settings: prospective preliminary report of ten patients - Fioretto, JR; Bonatto, Rossano César [UNESP]; Ricchetti, SMQ; Carpi, Mario Ferreira [UNESP]; de Moraes, M. A.; Padovani, Carlos Roberto [UNESP] (Medicinska Naklada, 2001)
Aim. To establish a protocol for the early introduction of inhaled nitric oxide (iNO) therapy in children with acute respiratory distress syndrome (ARDS) and to assess its acute and sustained effects on oxygenation and ventilator settings.Patients and Methods. Ten children with ARDS, aged 1 to 132 months (median, 11 months), with arterial saturation of oxygen <88% while receiving a fraction of inspired oxygen (FiO(2)) <greater than or equal to>0.6 and a positive end-expiratory pressure of greater than or equal to 10 cm H2O were included in the study. The acute response to iNO was assessed in a 4-hour dose-response test, and positive response was defined as an increase in the PaO2/FiO(2) ratio of 10 mmHg above baseline values. Conventional therapy was not changed during the test. In the following days, patients who had shown positive response continued to receive the lowest iNO dose. Hemodynamics, PaO2/FiO(2), oxygenation index, gas exchange, and methemoglobin levels were obtained when needed. Inhaled nitric oxide withdrawal followed predetermined rules.Results. At the end of the 4-hour test, all the children showed significant improvement in the PaO2/FiO(2) ratio (63.6%) and the oxygenation index (44.9%) compared with the baseline values. Prolonged treatment was associated with improvement in oxygenation, so that FiO(2) and peak inspiratory pressure could be quickly and significantly reduced., No toxicity from methemoglobin or nitrogen dioxide was observed.Conclusion. Administration of iNO to children is safe. iNO causes rapid and sustained improvement in oxygenation without adverse effects. Ventilator settings can safely be reduced during iNO treatment.
Keywords: child welfare; methemoglobin; multiple organ failure; nitric oxide; respiratory distress syndrome; ventilation, mechanical